THE IMPORTANCE OF SPIRITUAL EDUCATION IN THE EDUCATION OF A DEVELOPED GENERATION - Ochilova Nigora Ruzimuratovna; Odilova Nigora (TADQIQOTLAR, 2025)
Annotation: The spiritual-moral ideal is a value passed down from ancestors to generations.  The  traditions  of  the  nation  and  archeological  monuments  play  an important role in this. Because national traditions and archeological monuments are not only a factor that reflects the cultural life of the nation, but also a source of evidence of its spiritual values. Consequently, today it is possible to ensure the inheritance of the spiritual and moral ideal by preserving traditions and archeological monuments.